An Implementation and Evaluation of Web-Based Appointment System for the Mindanao State University – Main Campus - Azimah Disoma Ampuan; Reymark Devila Delena (Journal of Information System and Informatics, 2022)
The Office of the University President of the Mindanao State University in Marawi City has the reputation of being one of the busiest in the university. It handles a variety of concerns, ranging from employee matters to matters of concern coming from the other campuses in the university system. However, matters became greatly complicated when the pandemic began and the hard lockdowns that followed forced everyone to stay at home or work remotely. It was observed that an existing perennial problem at the Office of the President was a lack of an efficient system to handle appointments, which resulted in wasted time and tasks delayed or undone. Hence, the aim of the project was to improve client waiting time by implementing a web-based appointment system. The researcher used two (2) models: the System Usability Scale and Technology Acceptance Model to evaluate the system. As a result, the system has a high level of satisfaction with a percentage of 90.2 from the user based on the overall result from two (2) models used. Therefore, implementing a web-based appointment system will certainly improve client waiting time at the Office of the President and employees at the office can schedule appointments more conveniently.